2007
DOI: 10.1007/s10620-007-9946-6
|View full text |Cite
|
Sign up to set email alerts
|

Ginseng, the Root of Panax ginseng C.A. Meyer, Protects Ethanol-Induced Gastric Damages in Rat through the Induction of Cytoprotective Heat-Shock Protein 27

Abstract: Ginseng, the root of Panax ginseng C.A. Meyer, has been reported to exert preventive effects on gastropathy via anti-oxidative and anti-inflammatory actions. In this study, we investigated the protective effects of ginseng against ethanol-induced gastric damages in rat. To examine the preventive effect of ginseng, rats received two different ginseng extracts, A and B, 1 h prior to the administration of ethanol. Pretreatment of rats with ginseng extract A and B attenuated the ethanol-induced gastric lesions by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 33 publications
(32 reference statements)
3
24
0
Order By: Relevance
“…These low levels of expression likely indicate an important role for HSP27 in cellular homeostasis and gastric mucosa defense (33)(34)(35)(36). In accordance with previous results, we also found HSP27 expressed in majority of gastric mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…These low levels of expression likely indicate an important role for HSP27 in cellular homeostasis and gastric mucosa defense (33)(34)(35)(36). In accordance with previous results, we also found HSP27 expressed in majority of gastric mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ginseng had protective effects from alcohol-induced gastric damages in rats. Significant induction of cytoprotective heat-shock proteins HSP27 and HSP70 was found in the ginseng-administrated rats, which suggested that the restoration of these proteins might contribute to preventing alcohol-induced gastric injuries [96]. Therefore, red ginseng could be used as potential treatment of hangover and alcohol-induced reproductive and gastric toxicity due to its antioxidant activity.…”
Section: Panax Ginsengmentioning
confidence: 99%
“…Mice Amelioration of liver and brain alcohol injuries through decreasing L-γ-glutamyl transpeptidase and butyryl cholinesterase [76] Humans Decreased signs and symptoms of alcohol hangover [79] Essential oil and citral Mice Hepatoprotective property against AFLD by decreasing levels of D-glucurono-6,3-lactone, glycerol-3-phosphate, and pyruvic acid in serum [80] Opuntia ficus-indica Flavones and phenolics Cladode Humans Reduced hangover symptoms by inflammatory mediator production inhibition [88,89] Rats Suppression of liver damage induced by alcohol through ending free radical chain reactions or enhancing the endogenous antioxidant activities [90] Panax ginseng Ginsenosides Root Humans Relief from hangover symptoms through reduced expiratory and plasma alcohol levels and hangover severity [91] Linoleic acid Mice Alleviation of hangover through reduced alcohol and acetaldehyde levels and enhanced ADH and ALDH activities [92] Mice Suppressed alcohol-induced toxicity on male fertility [93] Ricefish Suppressed alcohol-induced toxicity on embryogenesis [94] Mouse embryos Suppressed alcohol-induced toxicity in the neurocranium through its effects on antioxidant activity [95] Rats Suppressed alcohol-induced toxicity in the gastric system via the restoration of heat-shock proteins [96] Hypericum perforatum Hypericin and hyperforin Leave and flowering tops Rats and mice Reduced voluntary alcohol intake in acute and chronic alcohol treatment through neurochemical mechanisms [101,104,105] Rats Attenuated alcohol withdrawal syndrome by inhibition of the effects on tremors and audiogenic seizures [102] Salvia miltiorrhiza…”
Section: -Gingerol Rhizomementioning
confidence: 99%
“…Extracts of T. wilfordii have been used as a traditional herbal therapy in Chinese medicine to treat different illnesses, but recent results have suggested that celastrol could be a potential agent to treat diseases such as Alzheimer disease (Chow et al 2013;Allison et al 2001). A study on the potential cytoprotective effect of ginseng indicated that pretreatment with ginseng prevented the ethanol-induced gastric lesions and decreased the level of apoptotic cell death in the rat gastric mucosa (Yeo et al 2008). Moreover, Hsp27 and Hsp70 were found to be overexpressed in ginseng-pretreated rats.…”
Section: Possible Mechanism Of Hsp Protection and Potential Therapeutmentioning
confidence: 99%